The student opportunities for AIDS/HIV research program: promoting public health leadership and transformation for undergraduate students through a principles-driven, cohort-based model - Johnson, Gabriel Lee; Neubauer, Leah C.; Bennett, Heidi; Bolivar, Andrea; Kirkland, Anna R.; Harper, Gary W. (Frontiers in Public Health, 2025)
IntroductionUndergraduate public health degrees have grown over 1,100% over the past 20 years, not including interdisciplinary scholars who are interested and do not major in the field, marking an opportunity for proactive public health leadership in this burgeoning group of people with potential futures as public health leaders. The Students Opportunities for AIDS/HIV Research Program (SOAR) is a 2-year program funded by the National Institute of Mental Health (NIMH), providing research training and leadership development to historically underrepresented college undergraduates as formerly defined by NIMH. SOAR prepares students for a future as interdisciplinary HIV researchers and leaders in diverse disciplines, including public health. Rooted in critical feminist values and utilizing a cohort model, a high impact practice (HIP; Opacich), SOAR demonstrates tremendous potential for developing collaborative, transformational leaders (Teitel) and an example of a multi-tiered mentorship model.MethodsSOAR is housed in the Institute for Research on Women and Gender, an interdisciplinary unit of the University’s Office of the Vice President for Research and is operated in partnership with a CEPH-accredited School of Public Health at an elite predominately white institution (PWI). The program is grounded in guiding principles that center the foundational work of Black feminist scholars and activists, as well as the scholarship of Transformative Education (hooks). The development of the various components of the program were guided by the expanded Social Cognitive Career Theory (eSCCT) pedagogical frameworks of cohort models (Opacich) and mentorship ecosystems (Endo).ResultsTo date, three out of the four cohorts have graduated from the SOAR program, with 90% matriculating into advanced degree programs. SOAR scholars have also co-authored 32 peer reviewed articles and delivered over 80 presentations or panels at conferences. SOAR scholars have matriculated into a diverse array of disciplinary programs, moving towards their next step towards becoming HIV and public health researchers and leaders.DiscussionApproaches to developing cohorts were employed in addition to leveraging key critical, feminist approaches including embracing difference as key to cohort and leadership development, identifying key collective struggles to build cohesion, fostering a community of care, and embracing diversity across numerous social and developmental locations within the cohort. The SOAR program provides not only key ley lessons outlined, but also an example for future programs to follow and engage in early HIV and public health research leadership development at the undergraduate level.